Evaluation of the potential of Trichoderma spp isolates as an in vitro inhibitor of the growth of three isolates of the genus Fusarium spp (Nexo Revista Científica, 2022)
The Trichoderma spp genus represents a very important group of organisms in modern agriculture because they inhibit the growth of phytopathogenic fungi. However, it has been published that its ecological behavior varies depending on the geographical region where it comes from. In this study, the ability of 17 native Trichoderma spp isolates to inhibit the in vitro growth of three Fusarium spp isolates was evaluated. For the isolation of the fungi, the serial dilution technique and the growth medium Papa Dextrose Agar (PDA) were used, later the antagonism against three isolates of Fusarium spp was evaluated by means of the dual culture technique. The three Fusarium spp isolates were molecularly identified as belonging to two F. equiseti isolates and one identified as Fusarium spp. The percentage of Radial Growth Inhibition (PICR) was determined; obtaining the following results T. harzianum, T. asperellum and T. virens presented the percentages of PICR with 81.57%, 79.62% and 78.62% respectively, surpassing the rest of the isolates. The isolates T. harzianum, T. asperellum and T. virens must be evaluated under greenhouse and field conditions to define effectiveness and establish applicability.